2022
DOI: 10.3928/1081597x-20220207-01
|View full text |Cite
|
Sign up to set email alerts
|

Trifocal IOL Implantation in Eyes With Previous Laser Corneal Refractive Surgery: The Impact of Corneal Spherical Aberration on Postoperative Visual Outcomes

Abstract: PURPOSE: To analyze corneal aberrations and factors affecting visual outcomes after implantation of a trifocal intraocular lens (IOL) in eyes previously treated with laser corneal refractive surgery. METHODS: This retrospective case series included 222 consecutive eyes implanted with the trifocal FineVision Micro-F IOL (PhysIOL) after laser corneal refractive surgery. The series was divided into two groups according to safety outcomes aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This is not surprising because an IOL with a negative SA increases the negative SA induced by prior hyperopic corneal ablation. Our group recently found poorer visual outcomes in eyes with a higher previous grade of hyperopic LCRS and more negative Z4(0) values when these eyes received a trifocal IOL with a negative SA [17]. However, the outcomes could be influenced not only by the SA of the IOL, but also other issues such as the design of the IOL.…”
Section: Discussionmentioning
confidence: 90%
“…This is not surprising because an IOL with a negative SA increases the negative SA induced by prior hyperopic corneal ablation. Our group recently found poorer visual outcomes in eyes with a higher previous grade of hyperopic LCRS and more negative Z4(0) values when these eyes received a trifocal IOL with a negative SA [17]. However, the outcomes could be influenced not only by the SA of the IOL, but also other issues such as the design of the IOL.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the visual acuity of the three different trifocal MIOLs does not seem to be affected by angle κ [ 10 , 21 ]. Cobo-Soriano et al also excluded angle K as a negative factor influencing CDVA in bioptics patients, although they underwent corneal refractive surgery before lens replacement [ 30 ]. In our study, no negative effects were evident in CDVA or SI even in MIOL patients with high angle κ magnitudes after LASIK enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of multifocal IOLs in the setting of prior LASIK surgery has been generally controversial due to scarce analysis, with limited studies and limited follow-up [14]. However, isolated recent studies have reported good safety and efficacy for trifocal IOLs in laser-corrected eyes [15 ▪ ,16]. One such study, a retroactive analysis of 222 eyes [15 ▪ ] examined outcomes of trifocal implantation in eyes with prior laser corneal refractive surgery.…”
Section: Multifocal Intraocular Lensesmentioning
confidence: 99%
“…However, isolated recent studies have reported good safety and efficacy for trifocal IOLs in laser-corrected eyes [15 ▪ ,16]. One such study, a retroactive analysis of 222 eyes [15 ▪ ] examined outcomes of trifocal implantation in eyes with prior laser corneal refractive surgery. About 5% of the eyes had a significant loss of corrected distance vision.…”
Section: Multifocal Intraocular Lensesmentioning
confidence: 99%